Pemberdayaan Kader Kesehatan dalam Deteksi Dini Risiko Abortus di Desa Y - Ula, Zumrotul; Thalib, Kiki Uniatri; Hijrah, Hijrah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Abortion, or spontaneous miscarriage, is a reproductive health problem that continues to contribute to maternal morbidity and mortality, especially in rural areas with limited access to health services. Early detection of abortion risk is crucial to prevent serious complications in pregnant women. Health cadres, as extensions of medical personnel in the community, have great potential in providing education and early detection of abortion symptoms. This community service program aims to increase the capacity of health cadres in Village Y to detect abortion risk early through training, simulations, and outreach. The activities were conducted using a participatory and evaluative approach. The results showed a significant increase in cadres' understanding of risk factors, early symptoms, and referral procedures for abortion cases. This program is expected to become a model for cadre empowerment in promotive and preventive efforts for maternal health issues at the village level.